Animation Advertising Dan Brand Love Terhadap Pengaruh Keputusan Pembelian Pocari Sweat (Mahasiswa Angkatan 2021 Politeknik Negeri Malang) - Muhammad Adam Ramadhan Haris; Baroroh Lestari (CV. ITTC INDONESIA, 2024)
Various social and cultural issues have arisen as a result of the development of advertising among today's consumers. These are mainly related to the signs used, the images shown, the information conveyed, the meanings derived, and how they impact on people's perceptions, understanding, and behavior. Advertising aims to shape, strengthen, or change perceptions, attitudes, opinions, emotions, or beliefs embedded in belief systems. The objective of this study is to find out the influence of Animation Advertising and Brand Love on Purchasing Decisions for Pocari Sweat for students of the 2021 State Polytechnic of Malang’s cohort. This research was quantitative research with the variables Animation Advertising (X1), Brand Love (X2), and Purchasing Decisions (Y). This study used a questionnaire as the data collection method which was distributed to 100 respondents who are students of the 2021 State Polytechnic of Malang’s cohort using purposive sampling method. Data analysis in this study used multiple linear regression analysis. The results of partial hypothesis testing, Animation Advertising and Brand Love have a positive and significant effect on purchasing decisions. The results of simultaneous hypothesis testing show that animation advertising and brand love have a positive and significant effect on purchasing decisions.